The Impact of Residual O2, Temperature, and Light at Display on Sensory Attributes of Sliced, Packaged Salami - Mari Øvrum Gaarder; Mats Carlehög; Per Berg; Oddvin Sørheim; Hanne Larsen (Journal of Food Quality)
The aim of the study was to examine if small amounts of oxygen (O2) causing discolouration of salami exposed to light in the grocery store also cause adverse changes in the flavour and odour sensory profile. Sensory properties of packaged sliced salami under different temperatures (4, 20°C, and 23°C), two lights sources (LED and fluorescent), and a low level of residual O2 in the headspace were evaluated. The experiment consisted of nine series, which were sensory-assessed after 3 and 6 days of display. A combination of light exposure and residual O2 causing discolouration resulted in substantial off-flavour and off-odour of the displayed salami, both on the upper slice exposed to light and the middle slice in the stack with no direct light exposure. Samples from all other series without O2 and those displayed in various light or stored in darkness showed no changes in quality compared with control samples stored in darkness. Temperature at display did not affect sensory attributes in the series without O2 in the headspace. Sensory results from 3 to 6 days display were similar. To minimize quality defects and food waste, producers and retailers are advised to store packages of sliced salami in darkness until nearly all residual O2 is consumed internally by the product before placing the packages upon light in the counter.